Conductive polymer composition and use thereof
The conductive polymer composition with polythiophene, dispersible metals, and polyvinyl alcohol stabilizes surface resistance, addressing oxidation issues in conventional materials for improved conductivity and durability.
Patent Information
- Application Number
- JP2023121016
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-02-06
AI Technical Summary
Conventional polythiophene-based conductive polymer materials with microstructured metals face an increase in surface resistance due to oxidation, limiting their stability and conductivity.
A conductive polymer composition comprising polythiophene with specific structural units, dispersible metals like silver nanowires, and polyvinyl alcohol, which stabilizes the film's conductivity by reducing oxidation.
The composition maintains a low and stable surface resistance, enhancing the durability and conductivity of the conductive polymer film, suitable for applications such as transparent electrodes.
Smart Images

Figure 2025017779000001 
Figure 2025017779000002 
Figure 2025017779000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive polymer composition and its uses. [Background technology]
[0002] Conductive polymer materials have been developed in which a π-conjugated polymer, such as polyacetylene, polythiophene, polyaniline, or polypyrrole, is doped with an electron-accepting compound as a dopant. Applications of the conductive polymer materials to, for example, antistatic agents, solid electrolytes for capacitors, conductive paints, radio wave shielding materials, electrochromic elements, electrode materials, thermoelectric conversion materials, transparent conductive films, chemical sensors, and actuators have been considered. Among these, polythiophene-based conductive polymer materials are practically useful in terms of chemical stability (see, for example, Patent Documents 1 and 2).
[0003] Examples of polythiophene-based conductive polymer materials include PEDOT:PSS aqueous dispersion solutions obtained by polymerizing 3,4-ethylenedioxythiophene (EDOT) in an aqueous solution of polystyrene sulfonic acid (PSS) as a dopant, and so-called self-doped conductive polymers that have a substituent (sulfo group, sulfonate group, etc.) that combines water solubility and doping action in the polymer main chain, either directly or via a spacer. Applications of these polythiophene-based conductive polymer materials to transparent electrodes are being considered (see, for example, Patent Document 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-152667 A [Patent Document 2] JP 2008-235645 A [Patent Document 3] JP 2009-205924 A Summary of the Invention [Problem to be solved by the invention]
[0005] A conventional transparent electrode made of a mixture of a polythiophene-based conductive polymer material and a microstructured metal has both high transparency and low surface resistance. However, there is room for improvement in that the surface resistance increases with oxidation of the microstructured metal.
[0006] An object of one aspect of the present invention is to provide a conductive polymer composition capable of producing a conductive polymer film which reduces an increase in surface resistance value and can stably maintain a low surface resistance value, as compared with conventionally known compositions. [Means for solving the problem]
[0007] Means for Solving the Problems The present inventors have conducted extensive research to solve the above problems, and as a result have found the conductive polymer composition shown below, thereby completing the present invention.
[0008] That is, one aspect of the present invention relates to a conductive polymer composition as described below.
[0009] [1] A conductive polymer composition comprising 0.01 to 10 mass % of polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), 0.01 to 1.0 mass % of dispersible metal (B), and 0.01 to 4 mass parts of polyvinyl alcohol (C) per 1 mass part of the dispersible metal (B).
[0010] [ka]
[0011] [In the above general formulas (1) and (2), R 2represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom. m represents an integer of 1 to 10. n represents 0 or 1.] [2] The conductive polymer composition according to [1], wherein the dispersible metal (B) is at least one dispersible metal selected from the group consisting of silver nanoparticles, silver nanoplates, silver nanowires, copper nanoparticles, copper nanoplates, and copper nanowires.
[0012] [3] The conductive polymer composition according to [1] or [2], wherein the dispersible metal (B) is a silver nanowire.
[0013] [4] The conductive polymer composition according to any one of [1] to [3], wherein the content of the polythiophene (A) is 0.1 to 5 mass %.
[0014] [5] The conductive polymer composition according to any one of [1] to [4], wherein the content of the dispersible metal (B) is 0.01 to 100 parts by mass per part by mass of the polythiophene (A).
[0015] [6] The conductive polymer composition according to any one of [1] to [5], further comprising an amine compound (D).
[0016] [7] A method for producing a conductive polymer film, comprising applying the conductive polymer composition according to any one of [1] to [6] to a support and then drying the applied conductive polymer composition.
[0017] [8] A conductive polymer film comprising: polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2); a dispersible metal (B); and polyvinyl alcohol (C).
[0018] [ka]
[0019] [In the above general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom. m represents an integer of 1 to 10. n represents 0 or 1.] Effect of the Invention
[0020] One aspect of the present invention is to provide a conductive polymer composition capable of producing a conductive polymer film that reduces an increase in surface resistance value and can stably maintain a low surface resistance value, as compared with conventionally known compositions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] An embodiment of the present invention will be described in detail below. In this specification, the symbol "to" means a numerical range including both ends of the symbol.
[0022] As described above, the conductive polymer composition according to one embodiment of the present invention can provide a conductive polymer film having a lower surface resistance than conventionally known compositions.
[0023] The conductive polymer composition according to one embodiment of the present invention exhibits excellent durability and is significantly effective in suppressing oxidative deterioration of the dispersible metal.
[0024] A conductive polymer film produced using the conductive polymer composition can be used, for example, as a transparent electrode and a transparent conductive film.
[0025] The conductive polymer composition according to one embodiment of the present invention is characterized in that it contains 0.01 to 10 mass % of polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), contains 0.01 to 1.0 mass % of dispersible metal (B), and further contains 0.01 to 4 parts by mass of polyvinyl alcohol (C) per part by mass of the dispersible metal (B).
[0026] [ka]
[0027] [In the above general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom. m represents an integer of 1 to 10. n represents 0 or 1.] In the above general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom.
[0028] The linear or branched alkyl group having 3 to 6 carbon atoms is not particularly limited, but examples thereof include an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a cyclopentyl group, an n-hexyl group, a 2-ethylbutyl group, and a cyclohexyl group.
[0029] The above R 2 With regard to , in terms of exhibiting excellent durability, a hydrogen atom, a methyl group, an ethyl group, or a fluorine atom is preferred, and a hydrogen atom or a methyl group is more preferred.
[0030] In the above general formulas (1) and (2), m represents an integer of 1 to 10, and is preferably an integer of 1 to 6, more preferably an integer of 1 to 4, and even more preferably 2 or 3, in terms of exhibiting excellent durability properties.
[0031] In the above general formulas (1) and (2), n represents 0 or 1, and is preferably 1 in terms of exhibiting excellent durability properties.
[0032] The structural unit represented by the above general formula (2) represents the doped state of the structural unit represented by the above general formula (1).
[0033] Dopants that cause an insulator-metal transition by doping can be divided into acceptors and donors. The former enters the vicinity of the polymer chain of a conductive polymer by doping and takes away π electrons from the conjugated system of the main chain. As a result, a positive charge (hole) is injected into the main chain, so it is also called a p-type dopant. Conversely, the latter donates electrons to the conjugated system of the main chain, and these electrons move through the conjugated system of the main chain, so it is also called an n-type dopant.
[0034] In one embodiment of the present invention, the dopant is a sulfo or sulfonate group covalently bonded within the polymer molecule, and is a p-type dopant. Polymers that exhibit conductivity without the addition of an external dopant are called self-doped polymers.
[0035] The structural unit represented by the above general formula (1) or (2) is not particularly limited, but specific examples thereof include 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonic acid, 8-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)octane-1-sulfonic acid, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propanesulfonic acid, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propanesulfonic acid, ]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-ethyl-1-propanesulfonic acid, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propyl-1-propanesulfonic acid, or 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-butanesulfonic acid, and the like are exemplified.
[0036] Regarding the polythiophene (A) according to one embodiment of the present invention, which contains at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2), in terms of exhibiting excellent durability properties, it is preferable that the polythiophene (A) contains two or more repeats of at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2), and it is more preferable that the polythiophene (A) is composed of at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) and contains two or more repeats of the structural unit.
[0037] In one embodiment of the present invention, the conductivity of the polythiophene (A) is not particularly limited, but is preferably 0.01 S / cm or more as the conductivity (electrical conductivity) in a membrane state such as a film.
[0038] Note that, as the polythiophene (A) in one embodiment of the present invention, one synthesized based on publicly known information can be used.
[0039] In the conductive polymer composition according to one embodiment of the present invention, the concentration of the polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) is in the range of 0.01 to 10 mass%, with the total amount of the conductive polymer composition being 100 mass%. The concentration of the polythiophene (A) may be in the range of 0.1 to 5 mass%. From the viewpoint of excellent conductivity and operability, the concentration of the polythiophene (A) in the conductive polymer composition according to one embodiment of the present invention is preferably in the range of 0.02 to 7 mass%, more preferably in the range of 0.03 to 5 mass%, more preferably in the range of 0.03 to 3 mass%, and more preferably in the range of 0.03 to 2 mass%.
[0040] The conductive polymer composition according to one embodiment of the present invention is characterized in that it contains a dispersible metal (B) and has a concentration of 0.01 to 1.0 mass % relative to the total amount of the conductive polymer composition being 100 mass %. Due to this characteristic, a coating film having high conductivity can be obtained.
[0041] The dispersible metal (B) is not particularly limited, but specifically includes dispersible silver or dispersible copper. The shape of the dispersible metal is not particularly limited, and the shape of particles, fillers, plates, rods, pyramids, cubes, tubes, wires, fibers, particles, etc. can be used.
[0042] As the dispersible metal (B), from the viewpoint of excellent electrical conductivity, at least one dispersible metal selected from the group consisting of silver nanoparticles, silver nanoplates, silver nanowires, copper nanoparticles, copper nanoplates, and copper nanowires is preferable, and from the viewpoint of storage stability, dispersible silver nanowires are more preferable.
[0043] The preferred size of the dispersible metal (B) varies depending on its shape. For example, for nanoparticles, the particle diameter is preferably 1 to 1000 nm. For nanowires, the length is preferably 1 to 50 μm. For nanofibers, the diameter is preferably 1 to 100 nm and the length is 100 times or more the diameter. For nanorods, the diameter is preferably 1 to 100 nm and the length is 20 to 100 times the diameter. For nanocubes, the length of one side is preferably 1 to 200 nm. For nanoplates, the thickness is preferably 1 to 100 nm and the width is preferably 2 to 20 times the thickness.
[0044] The dispersible metal (B) is one that is dispersed or can be dispersed in an aqueous solvent or an organic solvent. That is, the conductive polymer composition according to one aspect of the present invention can be produced by blending a paste of the dispersible metal (B) or by blending a dispersion of the dispersible metal (B).
[0045] The conductive polymer composition according to one embodiment of the present invention is characterized in that it contains 0.01 to 1.0 mass% of dispersible metal (B) with the total amount of the conductive polymer composition being 100 mass%, and this content represents the content of the dispersible metal (B) itself. In other words, when the conductive polymer composition according to one embodiment of the present invention is produced using a dispersion of dispersible metal (B), components such as the solvent contained in the dispersion are not taken into account in the content of dispersible metal (B).
[0046] The content of the dispersible metal (B) is preferably 0.05 to 0.9 mass%, and more preferably 0.08 to 0.8 mass%, relative to the total amount of the conductive polymer composition being 100 mass%, in that it has high compatibility with the polythiophene (A) and can maintain high conductivity.
[0047] The content of the dispersible metal (B) is not particularly limited, but in terms of exhibiting excellent durability, it is preferably 0.01 to 100 parts by mass, more preferably 0.05 to 20 parts by mass, and more preferably 0.1 to 10 parts by mass, per part by mass of the polythiophene (A).
[0048] The conductive polymer composition according to one embodiment of the present invention contains polyvinyl alcohol (C). When the conductive polymer composition contains polyvinyl alcohol (C) together with the dispersible metal (B), oxidation of the dispersible metal (B) can be effectively reduced. Oxidation of the dispersible metal (B) increases the surface resistance of the conductive polymer film obtained from the conductive polymer composition. Therefore, by using polyvinyl alcohol (C), it is possible to obtain a conductive polymer composition that can stably maintain a low surface resistance, that is, a conductive polymer film having excellent durability can be produced.
[0049] Such conductive polymer films with excellent durability can provide transparent electrodes with long life spans, which can contribute to improving energy efficiency and thus achieving the Sustainable Development Goals (SDGs).
[0050] The concentration (content) of the polyvinyl alcohol (C) in the conductive polymer composition according to one embodiment of the present invention is not particularly limited, but in terms of exhibiting excellent durability properties, it is preferably in the range of 0.01 to 10 mass%, and more preferably in the range of 0.01 to 5.0 mass%, relative to the total amount of the conductive polymer composition being 100 mass%.
[0051] In addition, the content of the polyvinyl alcohol (C) is not particularly limited, but in terms of exhibiting excellent durability properties, it is preferably 0.01 to 4 parts by mass, more preferably 0.01 to 2 parts by mass, more preferably 0.01 to 1.5 parts by mass, and even more preferably 0.01 to 1 part by mass, per part by mass of the dispersible metal (B).
[0052] The conductive polymer composition according to one aspect of the present invention may further contain an amine compound (D), and preferably does so in that it exhibits excellent durability properties.
[0053] The above amine compound (D) is preferably ammonia or a primary, secondary or tertiary organic amine compound having a total of 1 to 16 carbon atoms.
[0054] Examples of the primary, secondary, or tertiary organic amine compound having a total carbon number of 1 to 16 include methylamine, dimethylamine, trimethylamine, ethylamine, triethylamine, normal-propylamine, isopropylamine, normal-butylamine, hexylamine, monoethanolamine, dimethylaminoethanol, methylaminoethanol, diethanolamine, N-methyldiethanolamine, triethanolamine, 3-amino-1,2-propanediol, 3-methylamino-1,2-propanediol, 3-dimethylamino-1,2-propanediol, 1,4-butanediamine, triisobutylamine, triisopentylamine, imidazole, 1-methylimidazole, 1,2-dimethylimidazole, pyridine, picoline, and lutidine.
[0055] By incorporating the amine compound (D) into the conductive polymer composition according to one embodiment of the present invention, the amine compound (D) reacts with the polythiophene (A) to become a conjugate acid of the amine compound (D), and an ammonium ion salt of the polythiophene (A) is prepared. The conjugate acid of the amine compound (D) is not particularly limited, and examples thereof include ammonium ions and primary, secondary, or tertiary ammonium ions having a total carbon number of 1 to 16. More specifically, examples of the conjugate acid of the amine compound (D) include ammonium ions, methylammonium ions, dimethylammonium ions, trimethylammonium, ethylammonium, triethylammonium, normal-propylammonium ions, isopropylammonium ions, normal-butylammonium ions, hexylammonium ions, 2-hydroxyethylammonium ions, N,N-dimethyl-N-(2-hydroxyethyl)ammonium ions, N-methyl-N-(2-hydroxyethyl)ammonium ions, di(2-hydro)ammonium ions, and the like. Examples of the ammonium ion include an N-dimethyl-N-(2,3-dihydroxypropyl)ammonium ion, ...
[0056] From the viewpoint of low coagulation property, the content of the amine compound (D) is preferably 0.01 to 10 mass%, more preferably 0.01 to 5 mass%, and still more preferably 0.01 to 3 mass%, relative to 100 mass% of the total amount of the conductive polymer composition.
[0057] When the conductive polymer composition according to one embodiment of the present invention contains the above amine compound (D), the polythiophene (A) containing at least one structural unit selected from the group consisting of structural units represented by the above general formula (1) and structural units represented by the general formula (2) can be described as a polythiophene (A) containing at least one structural unit selected from the group consisting of structural units represented by the following general formula (1') and structural units represented by the general formula (2').
[0058] [ka]
[0059] [In the above general formula (1') and general formula (2'), R 2 The definitions and preferred ranges of m and n are as shown in the above general formula (1) and general formula (2) R 2 The definitions and preferred ranges of m and n are the same as those of the corresponding amine compounds (D). M represents a conjugate acid of the amine compound (D). The conductive polymer composition according to one embodiment of the present invention may contain water in addition to the above-mentioned polythiophene (A), dispersible metal (B), polyvinyl alcohol (C), and amine compound (D), and preferably contains water in terms of excellent operability.
[0060] The water is not particularly limited, but examples thereof include distilled water, ion-exchanged water, RO water, and ultrapure water.
[0061] The water content is not particularly limited, but is preferably 60 to 99.9 mass%, more preferably 80 to 99.7 mass%, and even more preferably 95 to 99.5 mass%, with the entire conductive polymer composition including water being 100 mass%.
[0062] The conductive polymer composition according to one embodiment of the present invention may contain other additives (E) in addition to the above-mentioned polythiophene (A), dispersible metal (B), polyvinyl alcohol (C), amine compound (D), and water.
[0063] The other additives (E) are not particularly limited, but may include, for example, a binder, a surfactant, an organic solvent, etc. The other additives (E) may be used alone or in combination of two or more.
[0064] The binder is not particularly limited, but examples thereof include vinylpyrrolidone resin, acrylic resin, urethane resin, methyl methacrylate resin, styrene butadiene resin, vinyl acetate resin, polyamide resin, phenol resin, epoxy resin, melamine resin, thermosetting polyimide, or nitrocellulose or other cellulose resins.
[0065] The binder has a curing property and can assist in the formation of a film when the conductive polymer composition is formed into a film, etc. Examples of a method for curing the binder include thermal curing and UV curing.
[0066] The binder is preferably at least one selected from the group consisting of vinylpyrrolidone resin, urethane resin, acrylic resin, and epoxy resin, in terms of excellent film-forming properties.
[0067] In addition, when the conductive polymer composition according to one embodiment of the present invention contains the binder, the content of the binder is not particularly limited, but is preferably 1 to 1,500 parts by mass, more preferably 1 to 1,000 parts by mass, and still more preferably 1 to 500 parts by mass, relative to 1 part by mass of the polythiophene (A).
[0068] The surfactant is not particularly limited, but examples thereof include polymeric nonionic surfactants, amphoteric surfactants, fluorine-based surfactants, silicone-based surfactants, and acetylene glycol-based surfactants.
[0069] The amphoteric surfactant is not particularly limited, but examples thereof include betaine-type amphoteric surfactants, such as alkyl dimethyl betaine, lauryl dimethyl betaine, stearyl dimethyl betaine, and lauryl dihydroxyethyl betaine.
[0070] The fluorosurfactant is preferably one having a perfluoroalkyl group, and although there is no particular limitation, examples thereof include perfluoroalkanes, perfluoroalkyl carboxylic acids, perfluoroalkyl sulfonic acids, and perfluoroalkyl ethylene oxide adducts.
[0071] The silicone surfactant is not particularly limited, but examples thereof include polyether-modified polydimethylsiloxane, polyetherester-modified polydimethylsiloxane, hydroxyl group-containing polyether-modified polydimethylsiloxane, acrylic group-containing polyether-modified polydimethylsiloxane, acrylic group-containing polyester-modified polydimethylsiloxane, perfluoropolyether-modified polydimethylsiloxane, perfluoropolyester-modified polydimethylsiloxane, and silicone-modified acrylic compounds.
[0072] Fluorine-based surfactants and silicone-based surfactants are effective as leveling agents for improving the flatness of the coating film.
[0073] Specific examples of the above surfactants include the Olfin (registered trademark) series (manufactured by Nissin Chemical Industry Co., Ltd.), the Acetylenol (registered trademark) series (manufactured by Kawaken Fine Chemical Co., Ltd.), the Amizet (registered trademark) series (manufactured by Kawaken Fine Chemical Co., Ltd.), the Surflon (registered trademark) series (manufactured by AGC Seimi Chemical Co., Ltd.), and the Futergent (registered trademark) series (manufactured by NEOS Corporation).
[0074] When the conductive polymer composition according to one embodiment of the present invention contains the surfactant, the content of the surfactant is not particularly limited, but is preferably 0.0001 to 1 part by mass, more preferably 0.001 to 1 part by mass, and still more preferably 0.001 to 0.1 part by mass, relative to 1 part by mass of the polythiophene (A).
[0075] The organic solvent is not particularly limited, but may be, for example, alcohol, and more specific examples include methanol, ethanol, propanol, butanol, methoxyethanol, ethoxyethanol, butoxyethanol, and ethylene glycol.
[0076] In the conductive polymer composition according to one embodiment of the present invention, the concentration of components excluding water and organic solvents is preferably in the range of 0.1 to 20 mass%, more preferably in the range of 0.3 to 15 mass%, and still more preferably in the range of 0.5 to 10 mass%, relative to 100 mass% of the total amount of the conductive polymer composition.
[0077] The method for preparing the conductive polymer composition according to one embodiment of the present invention is not particularly limited, but may be, for example, a method of mixing a solution or solid of the polythiophene (A), a dispersible metal (B), polyvinyl alcohol (C), and water as necessary. At this time, the amine compound (D) and / or additive (E) may be further added and mixed as necessary. Note that each material is preferably added and dissolved in water or an organic solvent, and then mixed, but the order in which the materials are added and mixed is not particularly limited, and the conductive polymer composition according to one embodiment of the present invention can be prepared by mixing these materials in any order.
[0078] The temperature during mixing is not particularly limited, but may be, for example, room temperature (15 to 25° C.) or heated, preferably 0° C. or higher and 100° C. or lower.
[0079] The atmosphere in which the mixture is mixed is not particularly limited, and may be either air or an inert gas atmosphere.
[0080] In addition to the general mixing and dissolving operation using a stirrer tip or stirring blade, ultrasonic irradiation and homogenization treatment (for example, using a mechanical homogenizer, ultrasonic homogenizer, high-pressure homogenizer, etc.) may be performed during mixing. When homogenization treatment is performed, it is preferable to perform it at a low temperature in order to prevent thermal deterioration of the polymer.
[0081] The viscosity (20° C.) of the conductive polymer composition according to one embodiment of the present invention is preferably 200 mPa·s or less, more preferably 100 mPa·s or less, and further preferably 50 mPa·s or less.
[0082] The concentration of each component in the conductive polymer composition according to one embodiment of the present invention may be adjusted by the blending ratio, or may be adjusted by concentrating or diluting after blending. The concentrating method may be a method of distilling off the solvent under reduced pressure, or a method of using an ultrafiltration membrane.
[0083] A conductive polymer film according to one embodiment of the present invention contains the above polythiophene (A), the above dispersible metal (B), and the above polyvinyl alcohol (C).
[0084] The method for forming a conductive polymer film from the conductive polymer composition according to an embodiment of the present invention is not particularly limited, but may be, for example, a method in which the conductive polymer composition according to an embodiment of the present invention is applied to a support and then dried.
[0085] The support is not particularly limited as long as it is capable of applying the conductive polymer composition according to an embodiment of the present invention, and examples thereof include polymer substrates and inorganic substrates. Examples of polymer substrates include thermoplastic resins, nonwoven fabrics, paper, and resist film substrates. Examples of thermoplastic resins include polyethylene, polypropylene, polyethylene terephthalate, polyacrylate, and polycarbonate. Examples of nonwoven fabrics include natural fibers and synthetic fibers. Examples of paper include those mainly composed of general cellulose. Examples of inorganic substrates include glass, glass fibers, ceramics, aluminum oxide, and tantalum oxide.
[0086] Examples of the method for applying the conductive polymer composition include casting, dipping, bar coating, dispenser, roll coating, gravure coating, flexographic printing, screen printing, and offset printing.
[0087] The drying temperature for the coating film is not particularly limited as long as it is a temperature at which a uniform conductive polymer film is obtained and is equal to or lower than the heat resistance temperature of the substrate, but is preferably in the range of room temperature to 300°C, more preferably in the range of room temperature to 250°C, and even more preferably in the range of room temperature to 200°C.
[0088] The drying atmosphere may be any of air, inert gas, vacuum, and reduced pressure, but from the viewpoint of preventing deterioration of the conductive polymer film, an inert gas atmosphere such as nitrogen or argon is preferred.
[0089] The thickness of the resulting conductive polymer film is not particularly limited, but is preferably 10 -3 ~10 3 The range of 10 μm is preferable. -3 ~10 2 μm.
[0090] The conductive polymer film obtained from the conductive polymer composition according to one embodiment of the present invention has excellent conductivity and durability. Such a conductive polymer film can be suitably used, for example, as an electrode material, a transparent conductive film, and also as a radio wave shielding material. EXAMPLES
[0091] Examples of the present invention are given below.
[0092] The analytical instruments and measurement methods used in the examples are listed below.
[0093] (GC measurement) Equipment: Shimadzu, GC-2014 (NMR measurement) Equipment: VARIAN, Gemini-200 (Surface resistivity measurement) Equipment: Mitsubishi Chemical Loresta GP MCP-T600 or Mitsubishi Chemical Hiresta UX MCP-HT8000 (film thickness measurement) Equipment: DEKTAK XT manufactured by BRUKER.
[0094] [Method of producing conductive polymer film] The conductive polymer composition prepared in the Examples was applied to a polyester film (Cosmoshine A4100, manufactured by Toyobo Co., Ltd.) using a wire bar coater to form a coating film with a wet thickness of 12 μm. The coating was then dried by heating at 120° C. for 2 minutes in the atmosphere to obtain a conductive polymer film.
[0095] Example 1 In accordance with Synthesis Example 1 and Synthesis Example 2 of the known literature (JP 2019-196443 A), an aqueous solution containing 1.2 mass% of poly(3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid) (a polymer composed of a structural unit represented by the above general formula (1) and a structural unit represented by the above general formula (2), i.e., a polythiophene (A) according to one embodiment of the present invention, hereinafter referred to as "PT") was synthesized. The PT had a weight average molecular weight of 6,303 in terms of standard polystyrene measured by gel permeation chromatography, and contained iron ions and sodium ions at 10 ppm and 6 ppm (relative to the polymer), respectively.
[0096] 33.5g of the above aqueous solution (1), 40g of 0.5% by mass silver nanowire dispersion (T-AG147, manufactured by Seiko PMC) as dispersible metal (B), 0.1g of polyvinyl alcohol (C) (product code 163-03045, manufactured by Fujifilm Wako Pure Chemical Industries), 0.2g of 1-methylimidazole (product code M0508, manufactured by Tokyo Chemical Industry Co., Ltd., corresponding to amine compound (D)), and 0.05g of Olfine EXP4200 (manufactured by Nissin Chemical Industry Co., Ltd.) were added to 26.15g of pure water and stirred and mixed. As a result, a conductive polymer composition having a solid content concentration of polythiophene (A) of 0.40% by mass, a solid content concentration of dispersible metal (B) of 0.2% by mass, and a solid content concentration of polyvinyl alcohol (C) of 0.1% by mass was obtained. A conductive polymer film was prepared by the above method using the obtained conductive polymer composition, and after aging at room temperature in the atmosphere for 1 hour, the surface resistance value (initial surface resistance value) was measured. In addition, the surface resistance value (surface resistance value after test) of the obtained conductive polymer film was measured at room temperature in the atmosphere for 100 hours. The respective measurement results are shown in Table 1.
[0097] Example 2. 33.5g of the above aqueous solution (1), 40g of 0.5% by mass silver nanowire aqueous dispersion (T-AG147, manufactured by Seiko PMC) as dispersible metal (B), 0.2g of polyvinyl alcohol (C) (product code 163-03045, manufactured by Fujifilm Wako Pure Chemical Industries), 0.2g of 1-methylimidazole (product code M0508, manufactured by Tokyo Chemical Industry Co., Ltd., corresponding to amine compound (D)), and 0.05g of Olfine EXP4200 (manufactured by Nissin Chemical Industry Co., Ltd.) were added to 26.05g of pure water and stirred and mixed. As a result, a conductive polymer composition having a solid content concentration of polythiophene (A) of 0.40% by mass, a solid content concentration of dispersible metal (B) of 0.2% by mass, and a solid content concentration of polyvinyl alcohol (C) of 0.2% by mass was obtained. The conductive polymer composition thus obtained was used to prepare a conductive polymer film by the above-mentioned method, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 1.
[0098] Example 3. 33.5g of the above aqueous solution (1), 40g of 0.5% by mass silver nanowire dispersion (T-AG147, manufactured by Seiko PMC) as dispersible metal (B), 0.4g of polyvinyl alcohol (C) (product code 163-03045, manufactured by Fujifilm Wako Pure Chemical Industries), 0.2g of 1-methylimidazole (product code M0508, manufactured by Tokyo Chemical Industry Co., Ltd., corresponding to amine compound (D)), and 0.05g of Olfine EXP4200 (manufactured by Nissin Chemical Industry Co., Ltd.) were added to 25.85g of pure water and stirred and mixed. As a result, a conductive polymer composition having a solid content concentration of polythiophene (A) of 0.40% by mass, a solid content concentration of dispersible metal (B) of 0.2% by mass, and a solid content concentration of polyvinyl alcohol (C) of 0.4% by mass was obtained. The conductive polymer composition thus obtained was used to prepare a conductive polymer film by the above-mentioned method, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 1.
[0099] Example 4. 33.5g of the above aqueous solution (1), 50g of 0.5% by mass silver nanowire dispersion (Seiko PMC product name T-AG147) as dispersible metal (B), 0.5g of polyvinyl alcohol (C) (Fujifilm Wako Pure Chemical product code 163-03045), 0.2g of 1-methylimidazole (Tokyo Chemical Industry product code M0508, corresponding to amine compound (D)), and 0.05g of Olfine EXP4200 (Nissin Chemical Industry) were added to 15.75g of pure water and stirred. As a result, a conductive polymer composition having a solid content concentration of polythiophene (A) of 0.40% by mass, a solid content concentration of dispersible metal (B) of 0.25% by mass, and a solid content concentration of polyvinyl alcohol (C) of 0.5% by mass was obtained. The conductive polymer composition thus obtained was used to prepare a conductive polymer film by the above-mentioned method, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 1.
[0100] Comparative Example 1 33.5g of the above aqueous solution (1), 40g of 0.5% by mass of silver nanowire aqueous dispersion (Seiko PMC product name T-AG147) as dispersible metal (B), 0.2g of 1-methylimidazole (Tokyo Chemical Industry Co., Ltd., product code M0508), and 0.05g of Olfin EXP4200 (Nissin Chemical Industry Co., Ltd.) were added to 26.25g of pure water and stirred and mixed. As a result, a conductive polymer composition was obtained in which the solid concentration of polythiophene (A) was 0.40% by mass and the solid concentration of dispersible metal (B) was 0.2 mass%. A conductive polymer film was produced using the obtained conductive polymer composition by the above method, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 2.
[0101] Comparative Example 2 33.5g of the above aqueous solution (1), 50g of 0.5% by mass silver nanowire aqueous dispersion (Seiko PMC product name T-AG147) as dispersible metal (B), 0.2g of 1-methylimidazole (Tokyo Chemical Industry Co., Ltd., product code M0508), and 0.05g of Olfin EXP4200 (Nissin Chemical Industry Co., Ltd.) were added to 16.25g of pure water and stirred and mixed. As a result, a conductive polymer composition was obtained in which the solid concentration of polythiophene (A) was 0.40% by mass and the solid concentration of dispersible metal (B) was 0.25% by mass. A conductive polymer film was produced using the obtained conductive polymer composition by the above method, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 2.
[0102] Comparative Example 3. 33.5g of the above aqueous solution (1), 40g of 0.5% by mass silver nanowire dispersion (Seiko PMC product name T-AG147) as dispersible metal (B), 1g of polyvinyl alcohol (C) (Fujifilm Wako Pure Chemical product code 163-03045), 0.2g of 1-methylimidazole (Tokyo Chemical Industry product code M0508), and 0.05g of Olfine EXP4200 (Nissin Chemical Industry) were added to 25.25g of pure water and stirred. As a result, a conductive polymer composition was obtained in which the solid concentration of polythiophene (A) was 0.40% by mass, the solid concentration of dispersible metal (B) was 0.2% by mass, and the solid concentration of polyvinyl alcohol (C) was 1% by mass. The conductive polymer composition contains 5 parts by mass of polyvinyl alcohol (C) solid content per 1 part by mass of dispersible metal (B) solid content. A conductive polymer film was prepared using the obtained mixed solution by the above method, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 2.
[0103] Comparative Example 4. 33.5g of the above aqueous solution (1), 40g of 0.5% by mass silver nanowire aqueous dispersion (Seiko PMC product name T-AG147) as dispersible metal (B), 0.2g of polyacrylic acid (Fujifilm Wako Pure Chemical product code 165-18571), 0.2g of 1-methylimidazole (Tokyo Chemical Industry product code M0508), and 0.05g of Olfine EXP4200 (Nissin Chemical Industry) were added to 26.05g of pure water and stirred. As a result, a conductive polymer composition was obtained in which the solid concentration of polythiophene (A) was 0.40% by mass, the solid concentration of dispersible metal (B) was 0.2% by mass, and the solid concentration of polyacrylic acid was 0.5% by mass. A conductive polymer film was produced by the above method using the obtained conductive polymer composition, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 2.
[0104] Comparative Example 5. 33.5g of the above aqueous solution (1), 40g of 0.5% by mass silver nanowire aqueous dispersion (Seiko PMC product name T-AG147) as dispersible metal (B), 0.2g of guar gum (Tokyo Chemical Industry Co., Ltd. product code G0478), 0.2g of 1-methylimidazole (Tokyo Chemical Industry Co., Ltd. product code M0508), and 0.05g of Olfine EXP4200 (Nissin Chemical Industry Co., Ltd.) were added to 26.05g of pure water and stirred and mixed. As a result, a conductive polymer composition was obtained in which the solid concentration of polythiophene (A) was 0.40% by mass, the solid concentration of dispersible metal (B) was 0.2% by mass, and the solid concentration of guar gum was 0.5% by mass. A conductive polymer film was produced using the obtained conductive polymer composition by the above method, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 3.
[0105] Comparative Example 6. 33.5g of the above aqueous solution (1), 40g of 0.5% by mass silver nanowire aqueous dispersion (Seiko PMC product name T-AG147) as dispersible metal (B), 0.2g of 3-glycidyloxypropyltrimethoxysilane (Tokyo Chemical Industry Co., Ltd. product code G0210), 0.2g of 1-methylimidazole (Tokyo Chemical Industry Co., Ltd. product code M0508), and 0.05g of Olfin EXP4200 (Nissin Chemical Industry Co., Ltd.) were added to 26.05g of pure water and stirred. As a result, a conductive polymer composition was obtained in which the solid concentration of polythiophene (A) was 0.40% by mass, the solid concentration of dispersible metal (B) was 0.2% by mass, and the solid concentration of 3-glycidyloxypropyltrimethoxysilane was 0.5% by mass. The conductive polymer composition thus obtained was used to prepare a conductive polymer film by the above-mentioned method, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 3.
[0106] Comparative Example 7. 33.5g of the above aqueous solution (1), 40g of 0.5% by mass silver nanowire aqueous dispersion (Seiko PMC product name T-AG147) as dispersible metal (B), 0.2g of hydroxypropyl cellulose (Tokyo Chemical Industry Co., Ltd. product code H0386), 0.2g of 1-methylimidazole (Tokyo Chemical Industry Co., Ltd. product code M0508), and 0.05g of Olfin EXP4200 (Nissin Chemical Industry Co., Ltd.) were added to 26.05g of pure water and stirred and mixed. As a result, a conductive polymer composition was obtained in which the solid concentration of polythiophene (A) was 0.40% by mass, the solid concentration of dispersible metal (B) was 0.2% by mass, and the solid concentration of hydroxypropyl cellulose was 0.5% by mass. A conductive polymer film was produced using the obtained conductive polymer composition by the above method, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 3.
[0107] Comparative Example 8. 33.5g of the above aqueous solution (1), 0.2g of 1-methylimidazole (Tokyo Chemical Industry Co., Ltd., product code M0508), and 0.05g of Olfin EXP4200 (Nissin Chemical Industry Co., Ltd.) were added to 66.25g of pure water and mixed with stirring. As a result, a conductive polymer composition having a solid content concentration of polythiophene (A) of 0.40 mass% was obtained. A conductive polymer film was produced using the obtained conductive polymer composition by the above method, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 4.
[0108] Comparative Example 9. 40g of 0.5% by mass silver nanowire aqueous dispersion (T-AG147, manufactured by Seiko PMC) and 0.05g of Olfin EXP4200 (manufactured by Nissin Chemical Industry Co., Ltd.) were added as dispersible metal (B) to 59.95g of pure water and mixed by stirring. As a result, a conductive composition with a solid content concentration of dispersible metal (B) of 0.2% by mass was obtained. A conductive film was produced using the obtained conductive composition by the above method, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 4.
[0109] Comparative Example 10. 33.5g of the above aqueous solution (1), 0.2g of polyvinyl alcohol (C) (manufactured by Fujifilm Wako Pure Chemical Industries, product code 163-03045), 0.2g of 1-methylimidazole (manufactured by Tokyo Chemical Industry, product code M0508), and 0.05g of Olfin EXP4200 (manufactured by Nissin Chemical Industry) were added to 66.05g of pure water and stirred and mixed. As a result, a conductive polymer composition was obtained in which the solid content concentration of polythiophene (A) was 0.40 mass% and the solid content concentration of polyvinyl alcohol (C) was 0.2 mass%. A conductive polymer film was produced using the obtained conductive polymer composition by the above method, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 4.
[0110] Comparative Example 11. 40g of 0.5% by mass silver nanowire aqueous dispersion (T-AG147, manufactured by Seiko PMC) as dispersible metal (B), 0.2g of polyvinyl alcohol (C) (product code 163-03045, manufactured by Fujifilm Wako Pure Chemical Industries), and 0.05g of Olfin EXP4200 (manufactured by Nissin Chemical Industry Co., Ltd.) were added to 59.75g of pure water and stirred and mixed. As a result, a conductive composition was obtained in which the solid concentration of the dispersible metal (B) was 0.2% by mass and the solid concentration of the polyvinyl alcohol (C) was 0.2% by mass. A conductive film was produced using the obtained conductive composition by the above method, and the initial surface resistance value and the surface resistance value after the test were measured. The measurement results are shown in Table 4.
[0111] [Table 1]
[0112] [Table 2]
[0113] [Table 3]
[0114] [Table 4]
[0115] As shown in Tables 1 to 3, it was shown that the conductive polymer composition according to one embodiment of the present invention, which contains polythiophene (A), dispersible metal (B), and polyvinyl alcohol (C), can provide a conductive polymer film having low surface resistance and excellent stability.
[0116] Furthermore, as shown in Table 4, a low surface resistance value could not be obtained even when polyvinyl alcohol (C) was added to polythiophene (A) alone or organic solvent-dispersed metal (B) alone. This is believed to be due to the weakening of the conductive paths between the conductive materials.
[0117] [Additional Notes] The present invention is not limited to the above-described embodiments and examples, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in the different embodiments or examples are also included in the technical scope of the present invention. [Industrial Applicability]
[0118] The conductive polymer composition according to one aspect of the present invention forms a good conductive polymer film and exhibits high electrical conductivity, low surface resistivity, and excellent stability of the low surface resistivity, and is therefore expected to be applicable to antistatic agents, solid electrolytes for capacitors, conductive paints, radio wave shielding materials, electrochromic elements, electrode materials, thermoelectric conversion materials, transparent conductive films, chemical sensors, actuators, and the like.
Claims
1. A conductive polymer composition comprising 0.01 to 10 mass % of polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), 0.01 to 1.0 mass % of dispersible metal (B), and 0.01 to 4 mass parts of polyvinyl alcohol (C) per 1 mass part of the dispersible metal (B). 【Chemistry 1】 [In the above general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom; m represents an integer of 1 to 10; and n represents 0 or 1.
2. 2. The conductive polymer composition according to claim 1, wherein the dispersible metal (B) is at least one dispersible metal selected from the group consisting of silver nanoparticles, silver nanoplates, silver nanowires, copper nanoparticles, copper nanoplates, and copper nanowires.
3. The conductive polymer composition of claim 1 , wherein the dispersible metal (B) is a silver nanowire.
4. 2. The conductive polymer composition according to claim 1, wherein the content of the polythiophene (A) is 0.1 to 5 mass %.
5. 2. The conductive polymer composition according to claim 1, wherein the content of the dispersible metal (B) is 0.01 to 100 parts by mass per part by mass of the polythiophene (A).
6. The conductive polymer composition according to claim 1 , further comprising an amine compound (D).
7. A method for producing a conductive polymer film, comprising applying the conductive polymer composition according to claim 1 to a support and then drying the applied conductive polymer composition.
8. A conductive polymer film comprising: polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2); a dispersible metal (B); and polyvinyl alcohol (C). 【Chemistry 2】 [In the above general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom; m represents an integer of 1 to 10; and n represents 0 or 1.
Citation Information
Patent Citations
Solid-state electrolytic capacitor and manufacturing method therefor
JP2008235645A
Transparent conductive film, transparent conductive member, and silver NANO wire dispersion solution and manufacturing method of transparent conductive film
JP2009205924A
Conductive film
JP2011152667A
Cited By
Conductive polymers composition for infrared shielding and heat shielding and coating films using the same
KR102959952B1